Elucidating the gastroprotective mechanisms of Imperata cylindrica Beauv.var. major (Nees) C.E.Hubb through UHPLC-MS/MS and systems network pharmacology - Zhou, Jiaxin; Hu, Jianping; Liu, Jiancheng; Zhang, Wenchun (Scientific reports, 2024)
Imperata cylindrica Beauv.var. major (Nees) C.E.Hubb., commonly known as BaiMaoGen (BMG), a medicinal and edible traditional Chinese medicinal (TCM) herb commonly used in health supplements, has been observed to offer protective effects against gastrointestinal disorders. However, the specific bioactive compounds and their molecular mechanisms have not been fully elucidated. This study employed ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) and systematic network pharmacology to analyze and identify the key active components and their interactions with biological targets. Thirty-six main active compounds, including 3,4-dihydroxybenzoic acid and p -hydroxybenzoic acid, were identified and analyzed for their interaction with key protein targets using molecular docking and dynamic simulations. This combined approach highlighted the therapeutic pathways involved, particularly the PI3K/AKT signaling pathways, providing new insights into the molecular basis of BMG’s gastroprotective effects. Our findings suggested that BMG’s complex multi-target action can potentially be harnessed to develop effective treatments for gastrointestinal toxicity.